PENGARUH INTELLECTUAL CAPITAL DISCLOSURE DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR TAHUN 2017-2023 - Enggus Rivando; Rina Yuniarti; Hernadianto Hernadianto; Yudi Partama Putra; Yeni Fitria (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the influence of Intellectual Capital Disclosure and Good Corporate Governance on firm value in manufacturing companies listed on the Indonesia Stock Exchange from 2017 to 2023. The research method used is quantitative with an associative approach. The data used are secondary data obtained from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique used the documentation method, while the data analysis technique used multiple linear regression with the help of SPSS software. The results show that Intellectual Capital Disclosure influences firm value with a significance value of 0.011 < 0.05. Good Corporate Governance also influences firm value with a significance value of 0.000 < 0.05. Simultaneously, Intellectual Capital Disclosure and Good Corporate Governance influence firm value with a significance value of 0.000 < 0.05 in the F-test. The conclusion of this study indicates that intellectual capital disclosure and the implementation of good corporate governance can influence the increase in firm value in manufacturing companies listed on the Indonesia Stock Exchange. Keywords:  Good Corporate Governance, Intellectual Capital Disclosure, Company Value, Manufacturing Companies, Corporate Governance